2021
DOI: 10.1186/s43141-021-00116-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performances of leucine-rich α-2-glycoprotein 1 and stem cell factor for diagnosis and follow-up of colorectal cancer

Abstract: Background Colorectal cancer (CRC) is one of the most frequently diagnosed tumors worldwide with high mortality and morbidity. There is an urgent need for biomarkers to improve the outcomes and early detection of CRC. The sensitivity of traditional CRC tumor markers (carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9)) is not ideal. The levels of leucine-rich-alpha-2-glycoprotein 1 (LRG1) and stem cell factor (SCF) were evaluated, but the combined value of both markers is uncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Positively correlates with tumour stage and size [ 184 , 191 , 193 , 228 , 229 ] Serum In conjunction with other biomarkers, suggested as diagnostic, prognostic, and follow-up factor. Associated with altered glycosylation [ 13 , 230 233 ] Tumour tissue Associated with cancer aggressiveness and vascular density. Proposed as diagnostic in general and prognostic for stage III colorectal cancer [ 180 , 184 , 197 ] Stool In conjunction with Hp, SYNE2, RBP4, FN1 and ANXA6, suggested for early detection of high-risk adenomas and colorectal cancer [ 234 ] Endometrial Tumour tissue Suggested as independent prognostic factor of stage and lymphatic metastasis [ 235 ] Esophageal Plasma Significantly elevated in esophageal squamous cell carcinoma and, in conjunction with alpha-2-HS-glycoprotein, proposed as biomarker for early diagnosis [ 236 ] Tumour tissue Closely correlated with worse clinical survival [ 237 ] Serum In combination with CRP and sIL-6R, suggested as biomarker to predict response to preoperative chemoradiotherapy [ 238 ] Gastric Serum and tumour tissue Proposed as prognostic factor.…”
Section: Reviewmentioning
confidence: 99%
“…Positively correlates with tumour stage and size [ 184 , 191 , 193 , 228 , 229 ] Serum In conjunction with other biomarkers, suggested as diagnostic, prognostic, and follow-up factor. Associated with altered glycosylation [ 13 , 230 233 ] Tumour tissue Associated with cancer aggressiveness and vascular density. Proposed as diagnostic in general and prognostic for stage III colorectal cancer [ 180 , 184 , 197 ] Stool In conjunction with Hp, SYNE2, RBP4, FN1 and ANXA6, suggested for early detection of high-risk adenomas and colorectal cancer [ 234 ] Endometrial Tumour tissue Suggested as independent prognostic factor of stage and lymphatic metastasis [ 235 ] Esophageal Plasma Significantly elevated in esophageal squamous cell carcinoma and, in conjunction with alpha-2-HS-glycoprotein, proposed as biomarker for early diagnosis [ 236 ] Tumour tissue Closely correlated with worse clinical survival [ 237 ] Serum In combination with CRP and sIL-6R, suggested as biomarker to predict response to preoperative chemoradiotherapy [ 238 ] Gastric Serum and tumour tissue Proposed as prognostic factor.…”
Section: Reviewmentioning
confidence: 99%
“…Additionally, LRG1 served as a biomarker to detect early high-risk adenomas as well as colorectal cancer (Sun et al, 2017;Komor et al, 2020;Kopylov , 2020). significantly decreased combined indexes of stem cell factor, LRG1, and platelet lymphocyte ratio could be detected in nontreated colorectal cancer patients (Fouda et al, 2021). Basic research results suggested that LRG1 promoted the cellular proliferation and apoptosis by modulating runt-related transcription factor 1 expression in colorectal cancer (Zhou et al, 2017).…”
Section: Part Four: Lrg1 Involved In Tumor Diseasesmentioning
confidence: 94%